The hits and misses of Namibia's attempt to implement the Ecosystem Approach to Fisheries (EAF) Management. Issue 1 (1st January 2021) - Iitembu, Johannes A.; Erasmus, Victoria N.; Uanivi, Uatjavi; Nakwaya, Dietlinde; Horaeb, Richard R.; Nangolo, Ester; Nashima, Festus P.; Iita, Theopolina K.; Mwandemele, Osmund
ABSTRACT: Ecosystem Approach to Fisheries (EAF) management is a concept aimed at the conservation and sustainable use of the entire ecosystem. While EAF is a noble approach, its implementation has been challenging. Although Namibia has committed to the implementation of EAF, only limited assessment has been done of Namibian fisheries management processes and instruments concerning EAF. A qualitative assesment was done to ascertain if the Namibian fisheries management processes and instruments conform to the EAF principles. Namibian fisheries management processes and instruments largely conform to the EAF principles, although there are notable areas needing improvements. The conformities were pronounced in the total allowable catch setting, rebuilding depleted stocks, minimizing bycatch, and fishing impact minimization. The polluter pays, and user pays principles were also applied. Areas that were found lacking in this study included setting the indicators for EAF and ecosystem integrity. The assessment also noted the absence of guidelines for the precautionary approach principle and a transparent policy for quota and right allocation processes. The strategies for managing transboundary fish species are also not formulated. Overall, this assessment showed the complexities and challenges that Namibia and other countries need to overcome to implement EAF successfully.